Narrativas em curso: subsídios para a formação de professores de português em contexto de acolhimento a estudantes migrantes e refugiados no ensino básico brasileiro - Yara Carolina Campos de Miranda (2021)
The background of this doctoral dissertation is the scenario of transnational migrations of the 21st century, which has positioned Brazil as one of the destinations of migrants and refugees that come from different parts of the world due to different migratory processes. The investigative work undertaken had as a general objective the analysis of the training process of three Linguistics undergraduate students and two Applied Linguistics graduate students – the latter, including this work’s teacher-researcher – throughout the class “Introduction to Studies in Portuguese as an Additional Language” (DISC2018-2), with a view to subsidizing the structuring of initial training courses for teachers of Portuguese as a Welcoming Language (PLAc) in the context of teaching to migrants or refugees enrolled in Brazilian Basic Education. In 2018, I taught the DISC2018.2 class at the Federal University of Minas Gerais (UFMG), in the College of Linguistics and Literature (FALE). Through a partnership signed between FALE and the city’s Education Secretariat (SMED-BH), in addition to theoretical classes at the university, students enrolled in DISC2018-2 carried out teaching practices in municipal schools in the city of Belo Horizonte and taught PLAc to migrant or refugee students. As part of their class activities, teachers-graduate students (PGs) wrote a reflective diary shared with me through Google Drive. Based on this diary, I followed their narratives and reflections on the work done with migrant or refugee students, making comments and giving them suggestions in order to contribute to a joint constitution of their training as teachers. The diaries written by two undergraduate and two graduate students – including mine – were analyzed after the completion of the DISC2018-2 course, focusing on the narratives written by the participants. This is an investigation based on the assumptions of the Indisciplinary Applied Linguistics (MOITA LOPES, 2006), characterized as an ethnographic and auto-ethnographic study, linked to the qualitative paradigm and interpretive approach. The participants' narratives, analyzed under indexing clues (WORTHAM, 2001; BIZON, 2013), pointed to the contributions of collaborative work between PGs and the teacher-researcher, in addition to emphasizing the importance of undergraduate students in Linguistics and Literature, who are already teachers or future educators, seeing themselves as agents of their own training. To this end, this study showed the importance that courses and classes aimed at teacher training for language teaching – in this context, for PLAc – make possible that the voices of undergraduates are more visible, also considering their knowledge as constituents of their own and their teachers/trainers training within the university context. In addition, the analyzes signaled a gap in Pedagogy, Literature and Linguistics programs in regard to teacher training on teaching PLAc to children. Finally, the need for an extended language education (CAVALCANTI, 2013) for these PLAc teachers, based on the interculturality approach (MAHER, 2007), and based on an ecology of knowledge (SOUSA SANTOS, 2007), became evident, so that this training is more consistent with the complexity and diversity of the current world.